The gap between athletes' and parents' perceptions of parental practices: The role of gender. (November 2022) - Lienhart, Noémie; Nicaise, Virginie
Abstract: Objectives: The present study explored the differences between athletes' and parents' perceptions of parental practices (i.e., active involvement, directive, pressure, praise, and understanding behaviours implemented by parents in the context of their child's sport) by considering athletes' and parents' gender. Design: cross-sectional study. Method: Parents (N = 352) and athletes (N = 256, M  = 14.72 years) completed a questionnaire to measure their perceptions of parental practices in sport. Zero-order correlations were computed for the entire sample and each sub-group (i.e., father-daughter, father-son, mother-daughter, and mother-son). One-level multilevel model (level 1: respondent) was computed to measure the influence of the respondent on the perceptions of parental practices. Two-level multilevel model (level 1: respondent, level 2: dyad) estimated the impact of the athletes' gender, parents' gender, and their interaction on the differences in perceptions. Results: Correlations highlighted relatively modest concordance between perceptions of parents and adolescents. Multilevel models showed that compared to athletes, parents reported significantly less frequent use for directive behaviours ( β  = −0.29) and more frequent use for active involvement ( β  = −0.18) and praise and understanding ( β = 0.27) . Correlations and multilevel models showed that the differences between athletes' and parents' perceptions of parental practices differed according to gender. The differences in perceptions of the directive behaviours ( β  = −0.22) and active involvement ( β  = 0.22) were higher when the father was involved in the dyad compared to the mother. Highlights: Athletes and parents reported parental practices with only modest concordance. Parents reported significantly lower scores for directive behaviours. Parents reported significantly higher scores for active involvement. Concordance differed according to gender. Mother-athlete dyads were more concordant overall compared to father-athlete dyads.